2020
DOI: 10.1007/s15010-020-01401-y
|View full text |Cite|
|
Sign up to set email alerts
|

2019 Novel coronavirus: where we are and what we know

Abstract: There is a current worldwide outbreak of a new type of coronavirus (2019-nCoV), which originated from Wuhan in China and has now spread to 17 other countries. Governments are under increased pressure to stop the outbreak spiraling into a global health emergency. At this stage, preparedness, transparency, and sharing of information are crucial to risk assessments and beginning outbreak control activities. This information should include reports from outbreak sites and from laboratories supporting the investigat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
337
0
28

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 483 publications
(385 citation statements)
references
References 24 publications
(27 reference statements)
3
337
0
28
Order By: Relevance
“…Wild animals and bats are considered as the natural reservoir hosts and play a crucial role in transmitting various viruses, including Ebola, Nipah, Coronavirus and others [6,15] . SARS-CoV-2 is the seventh member of the family coronaviruses, which is the beta-CoV with over 70% similarity in genetic sequence to SRAS-nCoV [16]. Like SARS-CoV, MERS-CoV, and many other coronaviruses, SARS-CoV-2 likely originated in bats, but it requires further confirmation whether pneumonia infected by the SARS-CoV-2 is transmitted directly from bats or through an intermediate host [9,17,18] .Recent research has found that the virus is 96% identical at the whole-genome level to a bat coronavirus, which means bats is the most possible host of the SARS-CoV-2 [17,18] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 2 more Smart Citations
“…Wild animals and bats are considered as the natural reservoir hosts and play a crucial role in transmitting various viruses, including Ebola, Nipah, Coronavirus and others [6,15] . SARS-CoV-2 is the seventh member of the family coronaviruses, which is the beta-CoV with over 70% similarity in genetic sequence to SRAS-nCoV [16]. Like SARS-CoV, MERS-CoV, and many other coronaviruses, SARS-CoV-2 likely originated in bats, but it requires further confirmation whether pneumonia infected by the SARS-CoV-2 is transmitted directly from bats or through an intermediate host [9,17,18] .Recent research has found that the virus is 96% identical at the whole-genome level to a bat coronavirus, which means bats is the most possible host of the SARS-CoV-2 [17,18] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
“…Also, Ji and colleagues [19] demonstrated that snack as possible virus reservoir for human infection. And Zhu et al [16] indicated that bats and minks maybe the two potential hosts of the novel coronavirus, while the minks may be the intermediate hosts of this virus. Subsequently, studies have shown that pangolins are potential intermediate hosts, but in general, intermediate hosts may have multiple hosts [20] .…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 99%
See 1 more Smart Citation
“…At the time of writing this commentary (February 2020), the death toll from the COVID-19 epidemic caused by coronavirus SARS-CoV-2, which emerged in late December 2019 in Wuhan, China (World Health Organization, 2019), has surpassed the combined death toll of the SARS (Severe Acute Respiratory Syndrome) epidemic of [2002][2003] and the MERS (Middle East Respiratory Syndrome) epidemic of 2013 combined (Mahase, 2020). This epidemic seems to be spreading at an exponential rate, with a doubling period of 1.8 days, and there are fears that it might progress to pandemic scales (Cheng & Shan, 2020).…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Basic reproduction number ( ) 0 R for the model can be established using the next generation matrix method [4,5]. The basic reproduction number ( ) 0 R is obtained as the spectral radius of matrix 1 ( ) FV − at disease free equilibrium point.…”
Section: Basic Reproduction Numbermentioning
confidence: 99%